RETRACTED: Prospects for the development of university-based scientific tourism - Miroshnichenko Alisa; Makarenko Vadim (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001